Evidence of clinical efficacy and pharmacological mechanism of N-butylphthalide in the treatment of delayed encephalopathy after acute carbon monoxide poisoning - Song, Huiping; Yue, Aochun; Zhou, Xudong; Han, Wei; Li, Qin (Frontiers in Neurology, 2023)
Objective. Based on network meta-analysis (NMA) and network pharmacology approaches, we explored the efficacy of different regimens for DEACMP from clinical efficacy and pharmacological mechanisms. Methods. Firstly, NMA was conducted to obtain the ranking of the efficacy of different regimens for the treatment of DEACMP. Secondly, the drug with a relatively high efficacy ranking was selected out and its mechanism of treatment for DEACMP was identified through a network pharmacology analysis. Based on protein interaction and enrichment analysis, we predicted the pharmacological mechanism of the drug for the treatment of DEACMP, and molecular docking was subsequently carried out to verify the reliability of the results. Results. The results of NMA revealed that a total of 17 eligible RCTs involving 1293 patients and 16 interventions were eventually included in our analysis. Mesenchymal stem cells (MSCs) + N-butylphthalide (NBP) significantly increased mini-mental state examination (MMSE) and barthel index (BI) scores; NBP + dexamethasone (DXM) was the most effective treatment in improving activity of daily living (ADL) scores; NBP significantly decreased national institutes of health stroke scale (NIHSS) scores; Xingzhi-Yinao granules (XZYN) had more advantages in improving montreal cognitive assessment (MoCA) scores, translational direct current stimulation (tDCS) had a significant effect in improving P300 latency and P300 amplitude and kinnado + citicoline had the most obvious effect in improving malondialdehyde (MDA). The NMA indicated significant efficacy of NBP for the treatment of DEACMP. Meanwhile, by network pharmacology analysis, we obtained 33 interaction genes between NBP and DEACMP, and 4 of them were identified as possible key targets in the process of MCODE analysis. 516 Gene ontology (GO) entries and 116 Kyoto Encyclopedia of Gene and Genome (KEGG) entries were obtained by enrichment analysis. Molecular docking showed that NBP had good docking activity with the key targets. Conclusion. NBP has a better therapeutic effect on DEACMP, it can stably bind ALB, ESR1, EGFR, HSP90AA1, and other targets, and it may play a role in treating DEACMP by modulating Lipid and atherosclerosis, IL-17 signaling pathway, MAPK signaling pathway, FoxO signaling pathway, PI3K-Akt signaling pathway.